Mobbing as an example of unethical behaviours at work - Nerka, Arleta (Annales. Etyka w Życiu Gospodarczym, 2019)
Currently, in the workplaces, the issues of behaviours classified as unethical or a violation of an employee’s dignity and personal rights are on the rise. Mobbing is one of the manifestations of such behaviours, described in the provisions of the Labour Code. The phenomenon of mobbing refers to the quality of interpersonal relationships at work and affects the operation of the entire organizational structure. This is a severe example of the violation of personal rights because such harassment is no less than a psychological terror affected by one or more persons against (typically) a single individual. The aim of this study is an analysis of mobbing, especially as regards the employer’s obligation to oppose mobbing practices. Ethical behaviour towards staff is not only a condition for observing the principles of community life in the work environment but it is the building block for creating a positive image of the employer in the business community. Mobbing behaviour impacts an organization’ image and poses several financial costs.